O forno cerâmico de Calheiros (Ponte de Lima) - Leal, Antonio J. Cunha; Cunha, Armandino Baptista da (Trabalhos de Antropologia e Etnologia, 2020)
The farm «Quinta do Paço» lies in the «freguesia» of Calheiros, concelho of Ponte de Lima , Viana do Castelo. It is a farm in which a beautiful manar house stands - a good specimen of the architecture called «minhota», that is the say, typical of the region. This architecture dates back to the XVIII century. However, the archaelogical remains scattered through the region reflect features that go back to the foundation of our nation. The pottery found there from the Roman period, is a sign of a«settlement» that may belong to the Roman «villae» - Facha, Ponte de Lima, and Vila Cova, Barcelos- which is, at the moment, the aim of our studies. The pottery furnace we have just found, needs to be identified through an accurate datting. Nevertheless, owing to its morphological specific features and to the caractheristics of the products existing there -- «imbrex» of mediaeval type- the furnace may be inserted, broadly speaking, in the mediaeval period.